A New and Efficient Approach to the Synthesis of Nicotine and Anabasine Analogues - Huang, Kun (2009)
[Image: see text] A straightforward and practical approach was established for the synthesis of nicotine and anabasine analogues by the cyclization of mesylated 1-(3-pyridinyl)-1,4, and 1,5-diol derivatives to form the pyrrolidino or piperidino fragments. Nicotine analogue (S)-15 was prepared with good enantioselectivity using the developed azacyclization procedure of nonracemic (R)-1-pyridin-3-yl-butane-1,4-diol, which was obtained by the borane-mediated reduction of ketone 12 in the presence of the spiroborate ester derived from diphenyl prolinol and ethylene glycol.